Design rules to establish a credible More‐Electric Engine baseline power architecture concept - Qiyang Zhang; Patrick Norman; Graeme Burt (IET Electrical Systems in Transportation)
Abstract The More‐Electric Engine (MEE), with its electrified engine auxiliary systems and increased multi‐shaft power offtake, is likely to become an increasingly central aspect of future More‐Electric Aircraft. Consequently, lightweight but resilient electrical power architectures are needed for these future MEE applications. However, whilst a range of MEE architectures exist in the research literature, no effective baseline architecture or standardised feature identification has been proposed to specifically address their unique design requirements. Accordingly, any underpinning technology‐focused research for critical MEE subsystems may ultimately have a reduced effectiveness without this credible baseline. Based on comprehensive design analyses, preliminary design requirements and anticipated operational modes, this article proposes key design rules for the formation of the first generic baseline MEE electrical power system architecture concept. Guidance is provided on features such as the number of power generation systems, the number and topologies of distribution channels, type of power conversion, essential load redundancy, and the location of emergency power supply. This article also provides full transparency of the design process so that key decision points can be revisited to capture application‐specific requirements and updates to certification requirements.